2019
DOI: 10.1111/jre.12638
|View full text |Cite
|
Sign up to set email alerts
|

Methodological quality and risk‐of‐bias assessments in systematic reviews of treatments for peri‐implantitis

Abstract: Background and Objectives The purpose of the present study was to evaluate the methodological quality and risk of bias in systematic reviews (SRs) on the effectiveness of peri‐implantitis treatments. Material and Methods We searched four electronic databases: MEDLINE, Web of Science, Cochrane Database of Systematic Reviews, and EMBASE. Previous SRs focusing on peri‐implantitis treatment published between 2010 and 2017 were identified. After literature screening, eligible SRs were qualitatively assessed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 53 publications
(249 reference statements)
2
24
0
Order By: Relevance
“…A few studies have used AMSTAR 2 on topics including dentistry ( Hasuike et al., 2019 ), acupuncture ( Zhang et al., 2018 ), Tai Chi in Parkinson's Disease ( Kedzior and Kaplan, 2019 ) and surgery ( Yan et al., 2019 ). They all demonstrated that the majority or all of the included SRs had low methodological quality and in the majority the overall confidence in the results of the SR was considered to be “critically low”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have used AMSTAR 2 on topics including dentistry ( Hasuike et al., 2019 ), acupuncture ( Zhang et al., 2018 ), Tai Chi in Parkinson's Disease ( Kedzior and Kaplan, 2019 ) and surgery ( Yan et al., 2019 ). They all demonstrated that the majority or all of the included SRs had low methodological quality and in the majority the overall confidence in the results of the SR was considered to be “critically low”.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with our results. However, three of studies using AMSTAR 2 had a low sample count of 5, 10 and 23 SR respectively ( Hasuike et al., 2019 ; Kedzior and Kaplan, 2019 ; Zhang et al., 2018 ) and only one study included more than 100 meta-analyses ( Yan et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence quality assessments, including study limitations, inconsistency of results, indirectness of evidence, imprecision and reporting bias, should be discussed together with effect size obtained from synthesis such as meta-analysis. In systematic reviews on treatment of peri-implantitis, quality assessments are often performed as a simple format evaluation and scarcely presented and discussed with impact [40].…”
Section: Discussionmentioning
confidence: 99%
“…Establishing a standard treatment protocol for peri-implantitis is an urgent task for the specialists' community. Clinical trials directed to this specific condition has proven extremely challenging for researchers, as dental implants are a high-cost medical option in many countries, and peri-implantitis may be classified as an asymptomatic iatrogenic disease [40]. In the meantime, the clear lack of well-defined protocols and gold-standard approaches to tackle peri-implantitis reiterate the importance of meticulous preventative strategies in an attempt to arrest or delay the onset of the disease [56].…”
Section: Discussionmentioning
confidence: 99%
“…The biological complications related to dental implants include peri-implant mucositis and peri-implantitis. There is no definitive evidence regarding the etiology and clinical countermeasures for these two biological complications [ 2 ]. Various risk indicators have been discussed, and etiological similarities between periodontal and peri-implant tissues have been of interest to clinicians and researchers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%